Strategi Pemasaran dalam Menarik Konsumen Wedding Organizer - Willy, Ricky Ricardo; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Marketing communications in business development is very important, as are the marketing activities of Ohana Enterprise Wedding Organizer. In this business, marketing is the key to increasing a company's consumers. The author's aim in conducting this research is to find out how the marketing communication strategy used by the Ohana Enterprise Wedding Organizer team builds consumer engagement and encourages purchasing decisions. In this research the author also uses several theories and concepts as a theoretical basis, namely communication strategy, marketing communication, marketing communication concepts, and marketing communication mix. This research approach is qualitative and uses case study methodology. Researchers have the data and information needed by conducting participant observation, in-depth interviews, documentation, and literature study. The research results show that the marketing communication strategy carried out by Ohana Enterprise Wedding Organizer shows the emergence of a desire to make purchases, build loyalty, and encourage audiences to recommend products to other parties. In fact, this method has also proven that it can help companies continue to exist during times of crisis such as Covid-19. Komunikasi pemasaran dalam perkembangan usaha sangatlah penting, Begitu juga dengan aktivitas marketing Ohana Enterprise Wedding Organizer. dalam usaha ini marketing sangat menjadi kunci dalam meningkatkan konsumen suatu perusahaan. Tujuan penulis melakukan penelitian ini adalah mengetahui bagaimana strategi komunikasi pemasaran yang dilakukan oleh tim Ohana Enterprise Wedding Organizer dalam membangun engagement konsumen sert mendorong keputusan pembelian. Dalam penelitian ini penulis juga memakai beberapa teori dan konsep sebagai landasan teoritis yaitu strategi komunikasi, komunikasi pemasaran, konsep komunikasi pemasaran, dan bauran komunikasi pemasaran. Pendekatan penelitian ini kualitatif dan menggunakan metodologi studi kasus. Peneliti mempunyai data dan informasi yang dibutuhkan dengan melakukan observasi partisipan, wawancara mendalam, dokumentasi dan studi pustaka. Hasil penelitian menunjukkan bahwa strategi komunikasi pemasaran yang dilakukan oleh Ohana Enterprise Wedding Organizer menunjukkan munculnya keinginan untuk melakukan pembelian, membangun loyalitas, serta mendorong audiens untuk merekomendasikan produk kepada pihak lain. Malah cara ini juga membuktikan dapat membantu perusahaan tetap eksis pada masa krisis seperti pada Covid-19.